Conducting Thermographic Inspections in Electrical Substations: A Survey - Pedro J. Zarco-Periñán; Fco Javier Zarco-Soto; Irene M. Zarco-Soto; José L. Martínez-Ramos (Applied Sciences, 2022)
Liberalization of the electricity market has forced the use of economic and efficient maintenance techniques. Thus, it is necessary to extend the useful life of the facilities in a perfect state of service, and with quality supply for customers. Furthermore, thermography is a maintenance technique that can be implemented quickly, has low cost, and is very effective in terms of the results provided. For this reason, it is very widespread within the electricity sector. As substations are critical facilities within the electrical supply, thermographic inspections are carried out on them very frequently. However, to ensure that the results obtained are reliable, a series of requirements must be met. A compilation of the complete process of the performance of a correct thermography in substations is shown. The factors that affect performing a correct thermographic inspection are indicated. These can be procedural, technical, and environmental. In addition, conditions for conducting thermographic inspections and the action to performed on a hot spot are indicated. The hot spot is usually identified with a current and wind speed other than nominal; these two variables can mask the true severity of the hot spot. For this reason, the extrapolation of the detected temperature to the nominal current conditions and in the absence of wind is carried out using a proposed formula. Finally, two examples of application of the proposed formula and the recommended action on them are exposed.